The Development of Children’s Learning Assistance Strategy in The Covid-19 Pandemic with a Positive Deviance Approach - Wiwin Hendriani; Rudi Cahyono; Herdina Indrijati (Universitas Ahmad Dahlan, 2023)
This study aims to help parents develop effective learning assistance strategies for their children's distance learning during COVID-19 pandemic. This study applies action research with a positive deviance approach, involving the transfer of knowledge and experiences of positive deviants, namely parents who have previously found adaptive assisting strategies. The participants consisted of parents of elementary school students, with children who are carrying out full learning from home. Data collection was carried out through interviews, focus group discussions, observation, and the use of documents via a google form, while the data analysis used thematic analysis techniques. The results obtained are in the form of a formulation of effective learning assistance strategies applied at home based on good parental practices during the COVID-19 pandemic, consisting of steps to overcome four specific challenges. All strategic steps formulated have a positive impact on both parents and children.